The use of information technology in small industrial companies in Latin America - the case of the interior of São Paulo, Brazil - De Oliveira, Otávio José [UNESP]; Fontana, Guilherme [UNESP] (World Scientific Publishing, 2010)
This chapter presents the results and a brief analysis of the results of a survey conducted by members of the Department of Production Engineering at São Paulo State University(UNESP). The survey analyzed the use and degree of satisfaction with computer resources in small companies in the Bauru region, SãoPaulo, Brazil. Sixty-eight organizations registered at the Center of Industries of the State of São Paulo (Bauru regional office) were surveyed by means of a questionnaire sent out by e-mail. The main focus of the study was in the production and supplies planning and control areas. Analysis of the data and business owner reports revealed the urgent need to develop low-cost computer programs, especially developed for management activities in small companies, providing increased competitive capacity.
Keywords: Information systems; Information technology; Latin America; Small and medium industries; São Paulo Brazil